The inflationary consequences of prioritising central bank profits - Stefan Gebauer; Sebastiaan Pool; Julian Schumacher (European Central Bank (ECB), 2024)
This paper examines the impact of rising interest rates on central bank profitability. Using a stylized income model, we demonstrate that changes in interest rates in combination with expansive balance sheet policies introduce a cyclical component into the central bank's profit and loss statement. Our findings reveal, however, that while the interplay of such policies may dampen short-term profitability if interest rates rise, they do not undermine a central bank's financial strength, because higher interest rates also raise the value of future seigniorage income. Using data for the euro area, we quantify the consequences for inflation of setting interest rates aimed at mitigating financial losses, showing that such a strategy would lead to substantially higher inflation rates. Overall, our findings confirm that a central bank's willingness to accept temporary losses reflects a commitment to price stability, rather than a hindrance.
Keywords: E31; E43; E52; E58; E63; 330; Monetary policy; central bank profitability; central bank independence